Corrigendum: Radio observations of the merging galaxy cluster Abell 520 (Astronomy and Astrophysics (2019) 622 (A20) DOI: 10.1051/0004-6361/201833900) - Hoang, D.N.; Shimwell, T.W.; Van Weeren, R.J.; Brunetti, G.; Röttgering, H.J.A.; Andrade-Santos, F.; Botteon, A.; Brüggen, M.; Cassano, R.; Drabent, A.; De Gasperin, F.; Hoeft, M.; et al. (EDP SCIENCES S A, 2019)
© ESO 2019. Some errors have occurred during the production of the original article. The left panel of Fig. 8 was incomplete. Here we publish the correct Fig. 8. Also, Eq. (5) was incorrect, it should read: (Figure Presented).